Hubungan Tinggi Badan Ibu, Riwayat Kekurangan Energi Kronis (KEK), dan Usia Ibu Saat Hamil dengan Kejadian Stunting pada Batita Usia 12-35 Bulan Di Desa Mojokerto, Kecamatan Kedawung, Kabupaten Sragen: The Correlation between Maternal Height, History of Chronic Energy Deficiency (CED) and Maternal Age During Pregnancy with Stunting Incidency in Toodlers Aged 12-35 Months in Mojokerto Village, Kedawung District, Sragen Regency - Ratna Noviyanti; Indri (UNIVERSITAS NGUDI WALUYO, 2023)
Stunting is a major nutritional problem in the world. Results of the Indonesian Nutrition Status Study (SSGI) for 2022, the prevalence of stunting in 2022 is 21.6%. Risk factor of stunting are maternal height, history of chronic energy deficiency (CED) and maternal age during pregnancy. The aim of this study was to analize the correlation between maternal height, history of chronic energy deficiency (CED) and maternal age during pregnancy with stunting accident in toodlers aged 12-35 month in Mojokerto Village, Kedawung District, Sragen Regency. This research was correlation analytic research with a cross-sectional approach. The population in this study are toddlers aged (12-35 months) total 163 toddlers in Mojokerto Village, Kedawung District, Sragen Regency. The Sample were taken by simple random sampling with 60 toddlers. Collecting data using a questionnaire and measuring length/height using a length board and stadiometer. Analysis data was using contingency koeficient test (α=0.05). Prevaletion of Stunting 30%. There is no correlation between maternal height, history chronic energy deficiency (CED), and maternal age during pregnancy with a stunting accident (p=0.610, p=431, p=450, respectively). There is no correlation between a maternal height, chronic energy deficiency (CED) and maternal age during pregnancy with a stunting accident in toodlers aged 12-35 months in Mojokerto Village, Kedawung District, Sragen Regency. ABSTRAK Stunting merupakan permasalahan gizi utama di dunia. Hasil Studi Status Gizi Indonesi (SSGI) tahun 2022 prevalensi stunting tahun 2022 sebesar 21.6%. Tinggi badan ibu, riwayat kekurangan energy kronis (KEK), dan usia ibu saat hamil merupakan faktor penybab terjadinya stunting. Tujuan penelitian ini adalah untuk mengetahui hubungan tinggi badan, riwayat kekurangan energy kronis (KEK), dan usia ibu saat hamil dengan kejadian stunting pada batita usia 12-35 bulan di Desa Mojokerto, Kecamatan Kedawung, Kabupaten Sragen.. Penelitian ini merupakan jenis penelitian analitik korelasi dengan pendekatan crossectional. Populasi pada penelitian ini adalah batita usia (12-35 bulan) berjumlah 163 batita di Desa Mojokerto, Kecamatan Kedawung, Kabupaten Sragen. Sampel ditentukan dengan menggunakan simple random sampling sejumlah 60 batita. Pengambilan data menggunakan kuesioner dan pengukuran panjang badan/tinggi badan menggunakan alat length board dan stadiometer. Analisis data menggunakan uji koefisinesi kontingensi (α = 0.05). Prevalensi stunting sebesar 30%. Tidak ada hubungan antara tinggi badan ibu, riwayat kekurangan energy kronis (KEK) dan usia ibu saat hamil dengan kejadian stunting (p=0.610, p=0.431, p=0.450).Tidak terdapat hubungan tinggi badan ibu, riwayat kekurangan energy kronis (KEK) dan usia ibu saat hamil dengan kejadian stunting pada batita usia 12-35 bulan di Desa Mojokerto, Kecamata Kedawung, Kabupaten Sragen.